(untitled) (International Journal of Architecture and Urbanism, 2025)
Since indicating the dynamic landscape, the site of the active area as Mount Merapi, people around the slopes have begun to develop new livelihoods through tourism. Since then, facilities have emerged to support the tourism sector on the slopes ranging from lodging to food stalls and souvenirs. But while growing tourism potential, the risk of Mount Merapi eruption still endangers all activities around Mount Merapi. From pyroclastic Flow, volcanic ash to hot lava flows can result in material losses to loss of life. Based on this phenomenon, it is necessary to have facilities that can accommodate tourism potential but still pay attention to the risk aspects of the eruption of Mount Merapi. The architecture response is a hotel, an experimental architectural model that can record the Merapi eruption’s impact on environmental conditions and protect tourists from eruption hazards. The result highlighted that the adaptable building approach is the direct approach applied to the design object. It was changing environmental conditions in the area with adaptive facades to meet the occupant safety aspects